Estudo comparativo entre a velocidade básica do vento estabelecida na NBR.6123 e a obtida de estações meteorológicas na Paraíba impactos nos âmbitos do projeto estrutural, do meio ambiente e dos custos - Ferreira, Enildo Tales (2015)
This study verified the possibility of adjusting the structural calculus parameters, namely basic wind velocity (V0) and its effects on buildings, as specified in NBR 6.123, to ventilation conditions in the state of Paraíba. Wind velocity data series collected in meteorological stations of Paraíba were analysed using Frechet s and Gumbel s probability distribution functions. The results demonstrate the need to re-examine those parameters, taking into account not only financial issues, but mainly environmental conservation, raw material waste reduction, and the resulting energy saving